Midwifery Care in the Postpartum Period with After Pains Discomfort at the Maternity Hospital: Asuhan Kebidanan pada Masa Nifas dengan Ketidaknyamanan After Pains di Rumah Sakit Bersalin - Wijaya, Ainur Rofi'ah Tiara; Hanum, Sri Mukhodim Faridah; Purwanti, Yanik (Universitas Muhammadiyah Sidoarjo, 2020)
The puerperium period begins after giving birth and ends when the uterus returns to its pre-pregnancy condition, in which six weeks the process occurs. After pains are the sensation of heartburn and produce pain that lasts during the puerperium due to periodic contractions and relaxation of the uterus which usually lasts two to four days. The results showed that the incidence of after pains was 50% in the 26-30 year age group and 40% in the third parity group. The purpose of this study was to determine postpartum care with discomfort after pain. Case study method using descriptive method. The case study was carried out at PMB Dadang Ratih Jambangan Sidoarjo which was conducted on December 30, 2019. Midwifery care was carried out by history taking, physical examination, diagnostic analysis, management and evaluation. The care provided went well without a hitch and there were no complications. The development of the research obtained is based on the accumulation of data from anamnesis to evaluation.